6-benzylaminopurine exposure induced development toxicity and behaviour alteration in zebrafish (Danio rerio). (1st June 2021) - Yang, Mengying; Qiu, Jinyu; Zhao, Xin; Feng, XiZeng
Abstract: 6-benzylaminopurine (6-BA) is one of the first synthetic hormones and has been widely used in fruit cultivation, gardening and agriculture. However, excessive use of 6-BA will cause potential harm to the environment and humans. Therefore, our research focused on assessing the impact of 6-BA on the development and neurobehavior of zebrafish. The results showed that 6-BA had little effect on the embryos from 2 hpf to 10 hpf. However, delayed development, decreased survival and hatchability were observed under 30 and 40 mg/L 6-BA from 24 hpf. 6-BA also reduced surface tension of embryonic chorions at 24 hpf. In addition, 6-BA caused abnormal morphology and promoted the accumulation of oxidative stress. Transcription of genes in connection with development and oxidative stress was also strikingly altered. Results of movement assay showed that zebrafish were less active and their behavior was significantly inhibited under the 20 and 30 mg/L 6-BA treatments. Locomotion-related genes th and mao were down-regulated by gradient, while the transcription of dbh was upregulated at a low concentration (2 mg/L) but decreased as the concentration increased. Moreover, 6-BA exposure caused increased arousal and decreased sleep. Sleep/wake related genes hcrt and hcrtr2 were upregulated, but decreased at 30 mg/L, while the mRNA level of aanat2 was reduced in a concentration-dependent manner. To sum up, our results showed that 6-BA induced developmental toxicity, promoted the accumulation of oxidative stress, and damaged locomotion and sleep/wake behavior. Graphical abstract: Image 1 Highlights: 6-BA induced delayed development and abnormal morphology. 6-BA reduced the surface tension of the chorion and promoted the accumulation of oxidative stress. 6-BA affected locomotion behavior. 6-BA caused increased arousal and decreased sleep.